Impact on direct and indirect costs of switching patients with inflammatory bowel disease from intravenous to subcutaneous infliximab (CT-P13). Issue 1 (22nd February 2023) - Carbery, Isabel; Burdge, Gemma; Clark, Tanya; Broglio, Giacomo; Greer, Dan; Alakkari, Alaa; Selinger, Christian Philipp
Abstract : Background: We aim to compare the real-life direct and indirect costs of switching patients from intravenous to subcutaneous (SC) CT-P13, an infliximab biosimilar, in a tertiary UK Inflammatory Bowel Disease (IBD) centre. Methods: All adult patients with IBD on standard dosing CT-P13 (5 mg/kg 8 weekly) were eligible to switch. Of 169 patients eligible to switch to SC CT-P13, 98 (58%) switched within 3 months and one moved out of area. Results: Total annual intravenous cost for 168 patients was £689 507.04 (direct=£653 671.20, indirect=£35 835.84). After the switch, as-treated analysis demonstrated total annual cost for 168 patients (70 intravenous and 98 SC) was £674 922.83 (direct = £654 563, indirect = £20 359.83) resulting in £891.80 higher cost to healthcare providers. Intention to treat analysis showed a total annual cost of £665 961.01 (direct = £655 200, indirect = £10 761.01) resulting in £1528.80 higher cost to healthcare providers. However, in each scenario, the significant decrease in indirect costs resulted in lower total costs after switching to SC CT-P13. Conclusions: Our real-world analysis demonstrates switching from intravenous to SC CT-P13 is broadly cost neutral to healthcare providers. SC preparations have marginally higher direct costs, switching allows for efficient use of intravenous infusion units and reduces costs to patients.